Crystal structures of free and ligand‐bound forms of the TetR/AcrR‐like regulator SCO3201 from Streptomyces coelicolor suggest a novel allosteric mechanism. (2nd September 2022) - Werten, Sebastiaan; Waack, Paul; Palm, Gottfried J.; Virolle, Marie‐Joëlle; Hinrichs, Winfried
Abstract : TetR/AcrR‐like transcription regulators enable bacteria to sense a wide variety of chemical compounds and to dynamically adapt the expression levels of specific genes in response to changing growth conditions. Here, we describe the structural characterisation of SCO3201, an atypical TetR/AcrR family member from Streptomyces coelicolor that strongly represses antibiotic production and morphological development under conditions of overexpression. We present crystal structures of SCO3201 in its ligand‐free state as well as in complex with an unknown inducer, potentially a polyamine. In the ligand‐free state, the DNA‐binding domains of the SCO3201 dimer are held together in an unusually compact conformation and, as a result, the regulator cannot span the distance between the two half‐sites of its operator. Interaction with the ligand coincides with a major structural rearrangement and partial conversion of the so‐called hinge helix (α4) to a 310 ‐conformation, markedly increasing the distance between the DNA‐binding domains. In sharp contrast to what was observed for other TetR/AcrR‐like regulators, the increased interdomain distance might facilitate rather than abrogate interaction of the dimer with the operator. Such a 'reverse' induction mechanism could expand the regulatory repertoire of the TetR/AcrR family and may explain the dramatic impact of SCO3201 overexpression on the ability of S. coelicolor to generate antibiotics and sporulate. Abstract : Crystallographic analysis of SCO3201 reveals an unusually compact ligand‐free state, incompatible with DNA‐binding, which is also observed in solution by small‐angle X‐ray scattering. An alternative conformation seen in a second crystal structure coincides with the presence of an unidentified ligand, a potential polyamine. The allosteric transition linking the two states is characterised by a remarkable α‐to‐310 transition within the hinge helix that physically connects the DNA‐binding and ligand‐binding domains.